Whom do we represent? A debate of engaged Roma on the Romani social position and anti-Romani racism in the Czech Republic and Slovakia - Berkyová, Renata; Ort, Jan (Romano džaniben, 2023)
The text is an edited transcript of a debate between engaged Roma from Slovakia and the Czech Republic - Renata Berkyová, Alice Sigmund Heráková, Vladimír Horváth, Michal Mižigár and Emílie Rigová. The participants in the discussion touch on the topics of the development of the Romani social position, emancipation of Roma, anti-Romani racism, class inequalities among Roma, the problems of Romani representation, the image of Roma in public space, the expectations placed on Roma in various areas of their work, and the preservation of Roma cultural heritage.